2021
DOI: 10.2147/jir.s312139
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Alleviated Osteoarthritic Progression in Rats Fed a High-Fat Diet by Inhibiting Apoptosis and Activating Autophagy via Modulation of MicroRNA-34a

Abstract: Purpose The mechanism underlying curcumin’s protective effect on osteoarthritis (OA) has not been clarified. This study aimed to determine whether curcumin exerts a chondroprotective effect by inhibiting apoptosis via upregulation of E2F1/PITX1 and activation of autophagy via the Akt/mTOR pathway by targeting microRNA-34a (miR-34a). Methods Male Sprague–Dawley rats were fed a normal diet (ND) or high-fat diet (HFD) for 28 weeks. Five rats from each diet group were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
18
1
Order By: Relevance
“…Curcumin is the most researched type of curcuminoid due to its potent antioxidant, anti-inflammatory, antimicrobial, antirheumatic, neuroprotective, anticancer, hepatoprotective, and cardioprotective properties [ 68 ]. Several studies have reported the pain-alleviating properties and the chondroprotective effects of curcumin and curcuminoids in clinical, in vivo, and in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin is the most researched type of curcuminoid due to its potent antioxidant, anti-inflammatory, antimicrobial, antirheumatic, neuroprotective, anticancer, hepatoprotective, and cardioprotective properties [ 68 ]. Several studies have reported the pain-alleviating properties and the chondroprotective effects of curcumin and curcuminoids in clinical, in vivo, and in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…Numerous in vivo models have validated the analgesic effects of curcuminoids and, in addition, provided mechanistic insights into their chondroprotective effects in an OA-induced rat model [ 61 , 62 , 63 ]. For example, curcumin supplementation in rats fed with a high-fat diet for 28 weeks inhibited apoptosis via increasing the expression of E2F1/PITX1; it also upregulated autophagy through the Akt/mTOR pathway by reducing the microRNA-34a [ 61 ]. In another recent study, a highly bioavailable formulation of curcumin (64.7 times more bioavailable) was tested for its protective effects against monosodium iodoacetate (MIA)-induced knee OA in rats [ 62 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…By establishing aging spontaneous OA and the destabilization of the medial meniscus (DMM) surgery-induced OA models in mice, Zhang et al found that curcumin treatment promoted autophagy by suppressing the protein kinase B/mechanistic target of rapamycin kinase (AKT/mTOR) signaling pathway enhanced autophagy and reduced apoptosis and cartilage loss ( Zhang et al, 2018a) . Yao et al established a rat model of OA by feeding a high-fat diet and injected curcumin into the knee joints of OA rats and found that the chondroprotective effect of curcumin may be achieved in part through inhibition of AKT/mTOR pathway autophagy ( Yao et al, 2021 ). Besides, there is a study confirming that curcumin has been used clinically and has been shown to improve pain in patients with mild to moderate OA.…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%
“…Immunofluorescence staining was used to detect the light chain 3 (LC3) level [ 30 ]. The tissue sections were incubated with the primary antibody LC3B (ab192890, 1:200, Abcam) for 12 h at 4°C, and subsequently incubated with Fluorescent-conjugated goat anti-rabbit IgG for 2 h at 37°C.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%